Pattern formation and wound healing - Maini, P (2002)
One of the main immediate challenges in the biomedical sciences is the synthesis of the vast amount of data now available at the molecular and cellular levels for development, regulation and repair. This, in turn, requires an understanding of the interaction and coordination of a myriad of complex inter-related processes occurring on very different spatial and temporal scales. Mathematics provides the obvious language in which to develop and interpret these interactions, and a number of mathematical models have already been proposed to account for certain observed biological and medical phenomena. Here, we consider two areas of modelling, namely spatial patterning, and wound healing, both sharing the common underlying processes of cell creating and responding to signalling cues.